The psychological experience of female caregivers of stroke patients in the rehabilitation period: A qualitative research (脑卒中康复期患者的女性照顾者心理体验的质性研究) - ZHANG Yingjie (张颖杰); LIU Xingling (刘兴玲); ZENG Wen (曾文); WANG Yilian (汪伊恋); LIU Qun (刘群); LI Yueer (黎月娥) (中西医结合护理)
Objective To explore the psychological experience and needs of female caregivers of stroke patients in rehabilitation period. Methods The phenomenological research method was used to conduct semi-structured interviews with 12 female caregivers of stroke patients. Results Based on the real experience of female caregivers during stroke rehabilitation period, four themes were extracted, including imbalance in physical and mental health, coping with multiple roles, insufficient of nursing information acquisition and lack of social support. Conclusion The feelings of female caregivers of patients in stroke rehabilitation stage are multi-dimensional, suggesting that we should pay attention to the mental health of female caregivers and guide them to seek positive coping styles, so as to provide better care for the rehabilitation of stroke patients. (目的 探讨脑卒中康复期患者的女性照顾者的照顾心理体验及需求。方法 采用现象学研究方法, 对12例脑卒中康复期患者的女性照顾者进行半结构式访谈, 采用质性研究的类属法进行整理和分析。结果 根据脑卒中康复期女性照顾者的真实体验提炼出4个主题: 身心健康失衡、多重角色应对失调、护理信息获取不足、社会支持缺乏。结论 脑卒中康复期患者的女性照顾者的感受呈现多维度, 提示应关注女性照顾者的心理健康, 引导其寻求积极的应对方式, 进而为脑卒中患者的康复提供更好的照护。)